A Numerical Study on Coconut Inflorescence Stem-Fiber-Reinforced Panels Subjected to Tensile Load, Compressive Load, and Flexural Load - Muralidhar Nagarajaiah; Raveesh Ranganathappa Mahadevaiah; Kishan Rao Bangri Parshuram; Pavan Hiremath (Engineering Proceedings)
Natural-fiber-reinforced composites are attracting an increasing amount of interest, and they are becoming more popular as a replacement for synthetic-fiber-reinforced composites. Natural-fiber-reinforced composites are important as a potential building material due to their lightweight nature, strength, and favorable qualities, which include eco-friendliness, non-toxicity, and biodegradability. Natural fibers such as hemp fibers, jute fibers, banana fibers, coconut fibers, sisal fibers, bamboo fibers, areca nut fibers, and kenaf fibers have been used for making composite panels because of their strength-to-weight ratio. Coconut inflorescence stem fibers are considered for our study. Coconut inflorescence stem-reinforced composite panels are often subjected to tensile load, compression load, and flexural load. Tensile strength, compressive strength, and flexural strength play a vital role when these panels are subjected to service loads. In this context, finite element analysis (FEA) is carried out on coconut inflorescence stem-reinforced panels subjected to tensile load, compressive load, and flexural load. A linear analysis is performed for the mechanical properties by using ANSYS workbench 2021 R1. A coconut inflorescence stem-reinforced composite specimen with the dimensions 280 mm × 25 mm × 3 mm (length × width × thickness) for tensile loading, 145 mm × 25 mm × 4 mm for the compressive load, and 150 mm × 25 mm × 4 mm for the flexural load is considered for the present study, as per the ASTM-D3039, ASTM-D3410, and ASTM-D790 standards, respectively. Finite element analysis results showed good correlation with the analytical results.